YAP/TAZ activation predicts clinical outcomes in mesothelioma and is conserved in in vitro model of driver mutations. Issue 2 (5th February 2023) - Cunningham, Richard; Jia, Siyang; Purohit, Krishna; Salem, Omar; Hui, Ning Sze; Lin, Yue; Carragher, Neil O.; Hansen, Carsten Gram
Abstract: The Hippo signalling pathway is dysregulated across a wide range of cancer types and, although driver mutations that directly affect the core Hippo components are rare, a handful is found within pleural mesothelioma (PM). PM is a deadly disease of the lining of the lung caused by asbestos exposure. By pooling the largest‐scale clinical datasets publicly available, we here interrogate associations between the most prevalent driver mutations within PM and Hippo pathway disruption in patients, while assessing correlations with a variety of clinical markers. This analysis reveals a consistent worse outcome in patients exhibiting transcriptional markers of YAP/TAZ activation, pointing to the potential of leveraging Hippo pathway transcriptional activation status as a metric by which patients may be meaningfully stratified. Preclinical models recapitulating disease are transformative in order to develop new therapeutic strategies. We here establish an isogenic cell‐line model of PM, which represents the most frequently mutated genes and which faithfully recapitulates the molecular features of clinical PM. This preclinical model is developed to probe the molecular basis by which the Hippo pathway and key driver mutations affect cancer initiation and progression. Implementing this approach, we reveal the role of NF2 as a mechanosensory component of the Hippo pathway in mesothelial cells. Cellular NF2 loss upon physiological stiffnesses analogous to the tumour niche drive YAP/TAZ‐dependent anchorage‐independent growth. Consequently, the development and characterisation of this cellular model provide a unique resource to obtain molecular insights into the disease and progress new drug discovery programs together with future stratification of PM patients. Abstract : Stratifying pleural mesothelioma (PM) patients reveals active YAP/TAZ is associated with poor clinical outcomes. An isogenic cell‐line model of PM driver mutations is developed that faithfully recapitulates clinical PM characteristics. NF2 regulates YAP/TAZ mesothelial activity in response to stresses, including sensing mechanical cues, while BAP1 appears to regulate a stem‐cell‐like transcriptional program.